2019
DOI: 10.1111/opn.12253
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness among older people living in care homes in Sri Lanka

Abstract: Aim and objectives The aim of this study was to explore loneliness in older people (aged 65+) living in care homes in Colombo, Sri Lanka. Background Loneliness, defined as the subjective, unwelcome feeling of the lack or loss of companionship, is known to be associated with old age, especially among older people living in care homes. Although several studies have shown that loneliness is highly prevalent, we lack knowledge about older people's personal experience of loneliness when residing in a care home and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 33 publications
0
26
1
Order By: Relevance
“…Of the 27 studies on emotional loneliness, seven studies explored emotional loneliness as a consequence of relational issues [132,136,138,142,148,153,155,157], further supporting the idea that social and emotional loneliness are interconnected. Four of these identified that complex family dynamics including responsibility for childcare, older children leaving home, and bereavement (for mothers) [132]; poor childhood attachment (to fathers), and weak sibling relationships [153]; being placed in a care home [148]; and loss of intimate partner relationships [136,155]. These all resulted in the deeply emotional character of loneliness connected to low mood, a lack of sense of purpose and feelings of suffering, family abandonment, and pervasive worry.…”
Section: Emotional Lonelinessmentioning
confidence: 82%
“…Of the 27 studies on emotional loneliness, seven studies explored emotional loneliness as a consequence of relational issues [132,136,138,142,148,153,155,157], further supporting the idea that social and emotional loneliness are interconnected. Four of these identified that complex family dynamics including responsibility for childcare, older children leaving home, and bereavement (for mothers) [132]; poor childhood attachment (to fathers), and weak sibling relationships [153]; being placed in a care home [148]; and loss of intimate partner relationships [136,155]. These all resulted in the deeply emotional character of loneliness connected to low mood, a lack of sense of purpose and feelings of suffering, family abandonment, and pervasive worry.…”
Section: Emotional Lonelinessmentioning
confidence: 82%
“…Older Finns are the most committed and active members of the Evangelical Lutheran Church of Finland (ELCF); nearly 80% of Finns age 65 and over and almost 90% of people older than 80 are members of ELCF (Evangelical Lutheran Church in Finland, 2020). Older people link religion and belonging, as practicing religion alleviates loneliness among the elderly (Wijesiri et al, 2019). As death approaches, the importance of religiosity varies from individual to individual; some find comfort in traditional Lutheran practices, whereas others turn to more personally constructed lived religion or individually meaningful spirituality (Saarelainen et al, 2020a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant impact of loneliness on older adults, the difficulty in identifying this problem remains an obstacle for healthcare professionals to take measures [27,28]. In relation to this, different studies have tried to find out the role of loneliness in both institutionalised and community-dwelling older adults [7,[29][30][31][32][33][34], comprehend healthcare professionals' experience on older adults' isolation [28] and evaluate strategies to reduce loneliness in older adults [35,36]. However, more research focusing on understanding healthcare professionals' perceptions of the phenomenon of loneliness in older adults is needed [28,37,38] since evidence suggests that healthcare professionals receive insufficient training to address this important issue [37,39,40].…”
Section: Introductionmentioning
confidence: 99%